PEMBANGUNAN WADUK JATIGEDE DAN MITOS-MITOSNYA DALAM SASTRA LISAN SUNDA - Yeni Mulyani (Jurnal Sosioteknologi, 2010)
Literature often reflects our lives, including the various situations we've ever experienced. "Jatigede Basin Development and Myth-myth in the Sunda Oral Literature" reveals a situation that occurred in the village of Cipaku, District Darmaraja, Sumedang. What is the construction of dams Jatigede and myth-myth? Did dam Jatigede nothing to do with myth? Then, if the myth is true Jatigede regarded by his supporters? This paper will describe it briefly. Keywords: myth, oral literature, and reservoirs Jatigede